Negative induction effect of graphite N on graphene quantum dots: tunable band gap photoluminescence1. Issue 34 (14th September 2015) - Zhu, Chong; Yang, Siwei; Wang, Gang; Mo, Runwei; He, Peng; Sun, Jing; Di, Zengfeng; Yuan, Ningyi; Ding, Jianning; Ding, Guqiao; Xie, Xiaoming
<x xml:space="preserve">Abstract</x> We synthesized nitrogen-doped graphene quantum dots (N-GQDs) under a high temperature range of 800–1200 °C and high pressure of 4.0 GPa through a solid-to-solid process.